Hybrid half-bridge package for high voltage application - Mouawad, Bassem; Li, Jianfeng; Castellazzi, Alberto; Johnson, Christopher Mark (2015)
3D power module structures allow for better cooling and lower parasitic inductances compared with the classical planar technology. In this paper, we present a hybrid half-bridge in a 3D packaging configuration, dedicated for high voltage application. A dynamic electrical test of the package is presented.